2022
DOI: 10.3390/jcm11133780
|View full text |Cite
|
Sign up to set email alerts
|

Using TBAg/PHA Ratio for Monitoring TB Treatment: A Prospective Multicenter Study

Abstract: The way to monitor tuberculosis (TB) treatment is extremely lacking in clinical practice. The aim of the study is to assess the role of the TBAg/PHA ratio in the treatment monitoring of TB. TB patients were followed up for 6 months and serial T-SPOT.TB (T-SPOT) assays were performed. In patients with successful treatment outcomes, the ESAT-6 sfc, CFP-10 sfc, and TBAg/PHA ratio all showed a decreased trend after the initiation of treatment. Conversely, PHA sfc showed an increased trend after 2 months of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The conclusion about a potential relationship between M. tuberculosis burden and impaired PHA-response was strengthened by the results that treatment normalized PHA-response within 6 weeks, a time frame that led to negative sputum smear/culture tests for approximately half of the patients. The finding of normalization under treatment confirmed recent findings although the time frame was longer [ 11 ]. In addition, although we did not detect significant differences between TB-SR and TB-RR under treatment, this did not exclude a relevance of treatment efficacy since the moderate size of subgroups limited the statistical power of this comparison.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The conclusion about a potential relationship between M. tuberculosis burden and impaired PHA-response was strengthened by the results that treatment normalized PHA-response within 6 weeks, a time frame that led to negative sputum smear/culture tests for approximately half of the patients. The finding of normalization under treatment confirmed recent findings although the time frame was longer [ 11 ]. In addition, although we did not detect significant differences between TB-SR and TB-RR under treatment, this did not exclude a relevance of treatment efficacy since the moderate size of subgroups limited the statistical power of this comparison.…”
Section: Discussionsupporting
confidence: 89%
“…Especially a combination of antigen-specific and PHA-induced IFN-γ expression from IGRAs (i.e., antigen/PHA ratios) gained promising results [6][7][8][9][10]. In addition, a recent study indicated potential capacity of antigen/PHA ratios to monitor efficacy of treatment [11].…”
Section: Introductionmentioning
confidence: 99%
“…High IL‐6 plasma levels decrease rapidly under treatment [20, 59], and normalisation was also seen for PHA‐induced response [92, 127]. In accordance, a recent study by Vivekanandan et al found that impaired PHA response in tuberculosis patients before treatment was associated with high IL‐6 plasma levels [92].…”
Section: The Role Of Il‐6 On Impaired T‐cell Response and Immunopatho...mentioning
confidence: 67%
“…Because of the opposite trends of IFN-γ response with different antigen conditions in NTM-LD and controls, we analyzed the ratio of various combinations of antigen stimulations. Calculation of ratios can eliminate the impact of individual IFN-γ variations on the ELISpot assay, and is also less affected by underlying host immune status [39,40]. In our multiparametric IFN-γ ELISpot assay we found that ratios of RD1/PPD, RD1/anti-CD3, and MTB300/ Candida can significantly differentiate nonprogressive and progressive NTM-LD.…”
Section: Plos Onementioning
confidence: 79%